CALCULATION BASED ON ESTIMATES OF PRICE FLUCTUATION DISK SELL DOLLARS WITH LINEAR REGRESSION ANALYSIS USING TURBO PASCAL - Fredy Flores; Ristyawati Ristyawati, SKom, MMSI (Jurnal Sistem Informasi, 2004)
At this writing will be given of the approximate or statistical forecasting in science.The estimate is used to find the relationship or linkage between the variable-variable,namely the unknown variables and variables that do not value or unknown value.To get an estimate or forecast value and the use of a correlation method and linearregression analysis in which the equation is obtained from the existing sample values.